Primary bone destruction and extracranial metastases in an atypical glioblastoma with sarcomatoid features. Issue 8 (18th August 2022) - Smaal, Johanna A; Postma, Alida A; Beckervordersandforth, Jan; Anten, Monique
Abstract : A man in his early 40s was referred to the neurology department with headache, hemianopsia and a palpable fluctuating mass on the back of his head. Investigations revealed a right-sided parieto-occipital mass with involvement of dura, bone and subcutaneous tissue. After debulking, pathological examination revealed a primary high-grade glioma with sarcomatoid features and a small-cell component. Concurrent chemoradiation was initiated. 10 weeks postoperatively, symptomatic bone metastases were diagnosed. During the clinical course, local and systemic treatment was consecutively administered, in order to control both primary tumour site and metastatic lesions. Due to progression of both intracranial and extracranial tumour load treatment was eventually discontinued; the patient passed away 28 months after initial presentation. The combination of a high-grade glioma with local destruction of the skull and subsequent metastasis is extremely rare and, when these features do occur, warrant a tailored approach to control both intracranial and extracranial tumour load.